FEATURES OF ANNUAL CYCLE IN THE LIFE OF BIRDS - qizi, Yusufjonova Munisa Abdumannob (Scholar Express Journals, 2021)
This article describes the period of existence of birds and their relationship with the environment. The life of a bird changes every year, just like other animals. And this is associated with a change in external factors, conditions of existence and has an important adaptive value. The life of a bird is in many ways different from the life of other animals. The body temperature of birds is higher than that of mammals (40 ° C and higher). This is due to the great mobility of the class of birds and causes a high metabolic rate.
Keywords: seasonal phases; non-nesting; breeding; nesting; post-nesting migrations; preparation for winter; wintering; molting; crepuscular; diurnal; seasonal cycles